Vegetation changes in the agricultural-pastoral areas of northern China from 2001 to 2013 - Wei SU; De-yong YU; Zhong-ping SUN; Jun-ge ZHAN; Xiao-xuan LIU; Qian LUO (Journal of Integrative Agriculture, 2016)
Climate change and human activity have resulted in increasing change of vegetation growth globally. Numerous studies have been conducted on extreme climate events and analyses of ecological environment evolution. However, such studies have placed little emphasis on vegetation change and spatial variation in this type of ecotone. Accordingly, this study analyzed the changes in vegetation type and growth using the 16-d composite MOD13A1 product with 1-km resolution and MOD12Q1 product with 1-km resolution. We used the mean, maximum, standard deviation normalized-difference vegetation index (NDVI) values, and the rate of change (ROC) of NDVI value to explain vegetation changes within the studied ecotone. Our results showed that significant vegetation type and growth changes have occurred in the study area. From 2001 to 2013, for example, with the exception of 2001, 2004 and 2009, a certain extent of grassland area was converted to cropland. Drought severity index (DSI) results indicate that there exists drought in 2001, 2004 and 2009. Such temporal changes in cropland and grassland area confirmed the ecological vulnerability of the ecotone. At the same time, vegetation varied spatially from west to east and from south to north. The mean, maximum and standard deviation NDVI values were all sorted in descending order based on differences in latitude and longitude, as follows: NDVI2013>NDVI2009>NDVI2004>NDVI2001